Metal-Organic Framework Co-MOF-74-Based Host-Guest Composites for Resistive Gas Sensing - Strauss, Ina; Mundstock, Alexander; Treger, Marvin; Lange, Karsten; Hwang, Seungtaik; Chmelik, Christian; Rusch, Pascal; Bigall, Nadja C; Pichler, Thomas; Shiozawa, Hidetsugu; Caro, Jürgen (ACS applied materials & interfaces, 2019)
Increasing demands in the field of sensing, especially for gas detection applications, require new approaches to chemical sensors. Metal-organic frameworks (MOFs) can play a decisive role owing to their outstanding performances regarding gas selectivity and sensitivity. The tetrathiafulvalene (TTF)-infiltrated MOF, Co-MOF-74, has been prepared following the host-guest concept and evaluated in resistive gas sensing. The Co-MOF-74-TTF crystal morphology has been characterized via X-ray diffraction and scanning electron microscopy, while the successful incorporation of TTF into the MOF has been validated via X-ray photoemission spectroscopy, thermogravimetric analysis, UV/vis, infrared (IR), and Raman investigations. We demonstrate a reduced yet ample uptake of CO2 in the pores of the new material by IR imaging and adsorption isotherms. The nanocomposite Co-MOF-74-TTF exhibits an increased electrical conductivity in comparison to Co-MOF-74 which can be influenced by gas adsorption from a surrounding atmosphere. This effect could be used for gas sensing.
Keywords: conducting MOFs; infiltration of MOFs; Guest@MOF; tetrathiafulvalene; gas sensing